De Sanctis - Cacchione Syndrome in a Male Ghanaian Child: A Case Report - Badoe, Ebenezer (Medical Research Archives, 2023)
A family was followed up after the presentation of a rare complication of xeroderma pigmentosum (De sanctis - cacchionne) syndrome in a child. A total of four children in a family of 8 developed the disease. The background of the family was explored revealing consanguinity as a result of cultural practices among the Mossi tribe in Ghana. Rare diseases are more common when there is consanguinity and this is the first report of this rare syndrome in Ghana and the West African sub region. The child showed the characteristic features of microcephaly, severe learning difficulties, cutaneous hypersensitivity, peripheral neuropathy and reported deafness. The disease predisposed the child to early squamous cell carcinoma of the eyelid. Advanced genetic testing showed complimentary group A in the sibling. Genetic counselling was offered. Management involved the dermatologists, opthalmologists and surgeons. This case report seeks to emphasise that consanguinity is linked to rare neurological diseases in Ghana and external collaborations in the field of advanced genetic testing can be mutually beneficial. The general recommended management options like sunblock, covering clothing UV film protection on windows are not possible in the tropics like Ghana. Rather support groups and genetic counselling are paramount.